Prevalence of Sperm Abnormalities and Factors Associated with Male Infertility in Douala, Cameroon - Nana, Théophile Njamen; Wabo, Bernard; Tchounzou, Robert; Moby, Herve Edouard Mpah; Assob, Clément Nguedia; Tchente, Charlotte Nguefack; Njamen, Cedric Nana; Panny, Christian; Okalla, Cecile Ebongue; Nsagha, Dickson Shey; Egbe, Thomas Obinchemti; Halle, Gregory Ekane (British Journal of Healthcare and Medical Research, 2023)
Introduction: Sperm abnormalities are common causes of male infertility in Cameroon. The causes of these abnormalities are multifactional. We described the prevalence of sperm abnormalities and to assess its associated risk factors among infertile participants visiting four hospitals in Douala. This multicentre descriptive study was carried out from the January 1rst 2010 to the December 31rst 2020 in four hospitals in Douala. The study enrolled 94 infertile participants aged between 25 to 53 years. Information from each consented participant was collected using a structure questionnaire. Following clinical examination, participants were referred for three consecutive spermograms. Data on the results of spermogram, demographic and clinical variables were summarized as frequencies and percentages using SPSS version 20. The frequency and percentage of each variable were presented on tables. This study enrolled 94 participants aged between 25 to 53 years (mean 39.21±10 years). Concerning the sperm abnormalities, most participants had Severe Oligoasthenozoospermia (62.7%), followed by those having severe Oligoasthenozoospermia with necrozoospermia (13.8%). The majority (60.6%) of them had Chlamydia trachomatis (titre IgG > 128) followed by 12.7% of others who had a varicocele. Severe Oligoasthenozoospermia was the most prevalent sperm abnormality and Chlamydia trachomatis was the most prevalent infectious risk factor. In Cameroon, the rate of male infertility is increasing but can be prevented by sustainable health education programme targeting exposure to socio-behavioural risk factors favouring sperm abnormalities.